Nontraumatic, sudden detachment of the mechanical prosthetic mitral valve after twelve years after primary operation - Bugajski, Paweł; Bartkowiak, Marek; Jedliński, Ireneusz; Kalawski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
In 1998 a 48-year-old patient underwent mitral and aortic valve replacement with mechanical prosthetic valves. Recovery was uneventful and the patient remained stable for 12 years. His prosthetic valve function was estimated by transthoracic echo (TTE) every year as routine follow-up. The TTE performed in July 2010 showed non compromised prosthesis function. In October 2011 the patient’s functional capacity began to deteriorate and he started experiencing episodes of shortness of breath. Further assessments showed perimitral leak, large tricuspid regurgitation (TR) and one diseased coronary artery that was treated with drug-eluting stent implantation. There were no symptoms of endocarditis or episodes of chest trauma. The patient was referred for surgery and after mitral exposure, detachment of the prosthetic valve along the mitro-aortic continuity was found. The tricuspid valve annulus was also severely dilated. The mitral prosthesis was explanted and a new mechanical prosthetic valve was implanted. TR was treated with ring implantation. After the operation the patient was referred to the intensive care unit on high doses of catecholamines and intra aortic balloon pump (IABP) augmentation. Recovery was prolonged but the patient was finally discharged on the 28th postoperative day with good heart function.